PLUVIOMETRIC VARIABILITY AND EXTREME PRECIPITATION AND DROUGHTS EVENTS IN THE CENTRAL NORTH MESOREGION OF PARANÁ - Caldana, Nathan Felipe da Silva; Rodrigues, Leonardo; Fujita, Thais; de Eiras, Marília Moreira; Ferreira, Luiz Gustavo Batista; de Aguiar e Silva, Marcelo Augusto (Revista Brasileira de Climatologia, 2021)
Extreme precipitation events cause severe damage in both urban and rural areas. The purpose of this work was to analyze rainfall variability and detect the extremes of precipitation and droughts occurrences and relate them to ENSO phenomena in the Central North Mesoregion of Paraná (MRNCP). We used data from 44 weather stations distributed in the area of the study, from 1976 to 2018. Based on the results, it was identified the precipitation has regional discrepancies, concentrating the highest rainfall in the southern portion. The highest annual precipitation was highly correlated with the periods identified as El Niño, and then in neutrality. There were large occurrences of drought by decent, with emphasis on the winter months, especially in August. High rainfall heights recorded within 24 hours in all regions analyzed, especially in the summer and spring months.